2014
DOI: 10.1096/fj.13-241208
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lipids do not contribute to the higher hepatic triglyceride levels of fructose‐ compared to glucose‐fed mice

Abstract: Fructose consumption has been associated with the surge in obesity and dyslipidemia. This may be mediated by the fructose effects on hepatic lipids and ATP levels. Fructose metabolism provides carbons for de novo lipogenesis (DNL) and stimulates enterocyte secretion of apoB48. Thus, fructose-induced hepatic triglyceride (HTG) accumulation can be attributed to both DNL stimulation and dietary lipid absorption. The aim of this study was to assess the effects of fructose diet on HTG and ATP content and the contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
24
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 41 publications
7
24
0
Order By: Relevance
“…Our hepatic gene expression analysis showed that HFD lowered the mRNA levels of PCSK9 and other SREBP2-target genes (HMGCR, SREBP2), while increasing SREBP1c gene expression in hamster liver. The inducing effect of HFD on transcription of lipogenic genes through activation of SREBP1c has been reported in other animal studies [14,18], our current study further linked fructose diet to deregulated SREBP2 pathway in hamsters. In mice, we did not observe elevated hepatic SPREBP1c mRNA levels in HFD group.…”
Section: Discussionsupporting
confidence: 82%
“…Our hepatic gene expression analysis showed that HFD lowered the mRNA levels of PCSK9 and other SREBP2-target genes (HMGCR, SREBP2), while increasing SREBP1c gene expression in hamster liver. The inducing effect of HFD on transcription of lipogenic genes through activation of SREBP1c has been reported in other animal studies [14,18], our current study further linked fructose diet to deregulated SREBP2 pathway in hamsters. In mice, we did not observe elevated hepatic SPREBP1c mRNA levels in HFD group.…”
Section: Discussionsupporting
confidence: 82%
“…This observation is in accordance with previous studies comparing the effects of glucose and fructose on liver lipid accumulation both in rodents [18,46,47] and in humans [48]. …”
Section: Discussionsupporting
confidence: 93%
“…Also in this study, the liver lipid pools became equally 13 C enriched in the glucose- and fructose-fed animals after the ingestion of 13 C-labeled lipids, but no control group fed with normal chow was included. It was furthermore demonstrated that plasma concentrations of apoB48 and apoB100 were similar between the glucose- and fructose fed groups [47]. Together, these results do not support the hypothesis that an increased influx of dietary lipids into the liver causes fructose-induced hepatic lipid accumulation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Other studies have shown that rats fed a fructose-rich diet have increased hepatic triglyceride and cholesterol levels [42], and fructose fed to rodents at supraphysiological doses induced steatosis and steatohepatitis by de novo lipogenesis [43]. Meta-analyses have also suggested that fructose consumption is related to the risk factors for metabolic syndrome, such as increased triglyceride levels, stimulated hepatic de novo lipogenesis, and increased visceral fat [44,45,46,47].…”
Section: Discussionmentioning
confidence: 99%